YOLOv8-ACU: improved YOLOv8-pose for facial acupoint detection - Yuan, Zijian; Shao, Pengwei; Li, Jinran; Wang, Yinuo; Zhu, Zixuan; Qiu, Weijie; Chen, Buqun; Tang, Yan; Han, Aiqing (Frontiers in Neurorobotics, 2024)
： Acupoint localisation is the most basic and important part of TCM acupuncture diagnosis and treatment. The recognition of facial acupoints using intelligent detection model can effectively improve the accuracy of localisation. In this research, we propose an improved YOLOv8-pose key point detection algorithm for facial acupoints, adding ECA attention to the model to improve the feature extraction ability of the acupoints, replacing the original neck module with a lighter Slim-neck module, and at the same time improving the loss function for GIoU, and the new model